Neuronal and Axonal Degeneration in Experimental Spinal Cord Injury: In Vivo Proton Magnetic Resonance Spectroscopy and Histology - Qian, Junchao (Mary Ann Liebert, Inc., 2010)
Longitudinal in vivo proton magnetic resonance spectroscopy ((1)H-MRS) and immunohistochemistry were performed to investigate the tissue degeneration in traumatically injured rat spinal cord rostral and caudal to the lesion epicenter. On (1)H-MRS significant decreases in N-acetyl aspartate (NAA) and total creatine (Cr) levels in the rostral, epicenter, and caudal segments were observed by 14 days, and levels remained depressed up to 56 days post-injury (PI). In contrast, the total choline (Cho) levels increased significantly in all three segments by 14 days PI, but recovered in the epicenter and caudal, but not the rostral region, at 56 days PI. Immunohistochemistry demonstrated neuronal cell death in the gray matter, and reactive astrocytes and axonal degeneration in the dorsal, lateral, and ventral white-matter columns. These results suggest delayed tissue degeneration in regions both rostrally and caudally from the epicenter in the injured spinal cord tissue. A rostral-caudal asymmetry in tissue recovery was seen both on MRI-observed hyperintense lesion volume and the Cho, but not NAA and Cr, levels at 56 days PI. These studies suggest that dynamic metabolic changes take place in regions away from the epicenter in injured spinal cord.